Genetic Diversity in the Italian Holstein Dairy Cattle Based on Pedigree and SNP Data Prior and After Genomic Selection - Ablondi, Michela; Sabbioni, Alberto; Stocco, Giorgia; Cipolat-Gotet, Claudio; Dadousis, Christos; Kaam, Jan-Thijs van; Finocchiaro, Raffaella; Summer, Andrea (Frontiers in Veterinary Science, 2022)
Genetic diversity has become an urgent matter not only in small local breeds but also in more specialized ones. While the maximization of genetic gain has reached astonishing levels thanks to the genomic era, it is counterbalanced by the potential loss of variability. Thus, in this study, we aimed to investigate the genetic diversity in the Italian Holstein breed using data from cows born between 2002 and 2020 by i) calculating the inbreeding based on pedigree and genotype data, ii) evaluating the changes in the effective population size throughout generations and iii) investigating the effect of different breeding strategies into genetic diversity. A total of 84,443 SNPs and 74,485 cows were kept after the quality control. Pedigree depth based on CGE was equal to 10.67. The average Fped was equal to 0.07 while the average FROH was more than double, being equal to 0.17. The pattern of the Ne based on pedigree and genotype data was similar although different in scale, with a constant decrease till last five generations. The overall inbreeding rate per year was equal to +0.27% and +0.44% for Fped and FROH throughout the studied period, which corresponds to a ~ 1.35% and ~ 2.2% 〖ΔF〗_gen, respectively. A significant increase in the ΔF was found since the introduction of genomic selection in the breed. The presented study in the Italian Holstein cattle showed the importance of controlling the loss of genetic diversity via the implementation of novel methodologies to ensure the long-term sustainability of the livestock production sector, as well as to guarantee future market demands.